Entrustable professional activities for the training of postgraduate primary care pediatricians - Villaizán Pérez, Carmen; Aparicio Rodrigo, María; Kovacs, Akos; Barak, Shimon; Calamita, Patrizia; Dejak Gornik, Katja; Jaeger-Roman, Elke; Kartousova, Beata; Katz, Manuel; Rafele, Innocenza; Reali, Laura; Reingold, Stephen; et al. (Academic medicine, 2023)
Problem - Competency-based training is a model of medical education program that uses an organized framework of competencies to develop entrustable professional activities (EPAs) for each specialty. Implementation of EPAs varies by medical specialty and country. Although national models for primary care pediatrics have been suggested in the past, standardized EPAs have not been established. - Approach - The authors, all members of the curriculum working group of the European Confederation of Primary Care Paediatricians, describe the development and design of a training model based on EPAs specifically for pediatricians in primary care. The objective was to facilitate and disseminate a training model that standardizes and improves training in primary care pediatrics. They aimed to make the model flexible enough so that it can be adapted to different training models and different European health systems. - Outcomes - Between May 2017 and December 2019, the authors developed a framework that includes 7 domains of competencies for the training in pediatric primary care and a set of 11 core EPAs to guide the learning process. They structured each EPA as follows: title, activity profile, domains of competence, competencies within each domain, required knowledge and skills, learning objectives described in terms of outcomes, and a 3-stage rating supervision scale to evaluate the level of performance. - Next Steps - The next step is the progressive implementation of these EPAs into the postgraduate primary care pediatrics training programs of European health systems. To support this implementation, the authors intend to develop training videos to assist in daily teaching of the EPAs. The authors will also develop a pan-European online resident forum designed specifically to facilitate EPA learning by sharing and discussing clinical cases. They plan to launch a pilot study on the use of the EPAs in primary care health centers in 6 European countries.
Zuerst online veröffentlicht 30. Dezember 2022
Gesehen am 22.06.2023